EVIDENCE OF ACCRUALS ANOMALY AROUND THE GLOBE - MUREȘAN, Diana (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
This paper reviews the empirical researchon accruals anomaly around the globe.Accruals anomaly is defined as the negative relation between accruals and future stock returns. Starting with Sloan (1996) many papers have documented and confirmed the existence of accruals anomaly in US capital market. Though, recent papers started to examine the existence of accruals anomaly outside the US.Overall, empirical results suggest that accruals anomaly is a global phenomenonpresent in developed countries with large companies and where an accruals accounting system exists. The approach adopted is a survey of the literature of accruals anomaly conducted on other samples than US companies. This review splits the discussion in three key topics: (1) empirical evidence from single country studies, (2) empirical evidencefrom comparative countries studies and (3) empirical evidencefrom US studies. This comparative discussion highlights the important challenges generatedbythe accruals anomaly in a global capital market. As a policy implication, investors from all over the globe should enhance their understanding of accruals information as accruals anomalyis a pervasive anomaly encountered in many capital markets.